Bearing Capacity of Geosynthetic Clay Liners for Cover Soils of Varying Particle Size. Issue 4 (1996) - Fox, P.J.; De Battista, D.J.; Chen, S.H.
Abstract : Geosynthetic clay liners (GCLs) are covered with soil after installation to protect them from stress concentrations due to construction activities and permanent structural loads. In this study, laboratory cover soil penetration tests (i.e. bearing capacity tests) were used to investigate the potential for lateral bentonite displacement within hydrated GCLs under concentrated loads. A greater cover thickness is required to adequately protect a GCL as the mean particle size of the cover soil increases. A ratio of cover soil thickness to breadth of loading area ( H/B ) between 1.0 and 1.5 is satisfactory for soils composed of sand and fine gravel. A larger H/B ratio is required for GCLs covered with clean medium-sized gravel. As compared to needle-punched products, adhesive-bonded and stitch-bonded GCLs show a greater tendency for lateral bentonite displacement under concentrated loads. If a hydrated GCL is protected by a suitably thick layer of cover soil, the results of this study show that the GCL will be undamaged by concentrated loads applied to the surface of the cover.